MENINGKATKAN KEMAMPUAN MEMERAGAKAN GERAK TARI KREASI BERDASARKAN POLA LANTAI DENGAN MEDIA AUDIO VISUAL - nda nur badiah (Jurnal Education and Development, 2019)
The purpose of this study is to improve the ability of students of Class X-MM.3 SMK Negeri 1 Pungging Mojokerto Even Semester Year Lesson 2018-2019 in Demonstrate Movement of Creation Dance Based on Floor Pattern with audio visual media. This study included a classroom action research with 2 cycles, each cycle consisting of plan, action, observation, reflection. The instruments used in this classroom action research are the Lesson Plans, study materials and materials. CD/flash, laptop and visual audio media infocus, questionnaires, observation sheets and rublics assessment. Audio Visual Media able to improve student ability of class X-MM.3 SMK Negeri 1 Pungging Mojokerto Even Semester Year Lesson 2018-2019 in modeling dance based on pattern.